Manual de identidad visual y contenido fotográfico para la marca de ropa Priscilia - Alcázar Peralta, Sharon Ifat (2022)
This project was born with the purpose of creating and conceptualizing a coherent and sustainable identity and personality for Priscilia, a brand that offers playful clothes for girls with a romantic style. From a visual identity and brand concept we seek to transmit, through each graphic piece and visual, love, romanticism and sweetness. As a starting point, an identity manual was developed with the purpose of transmitting the essence and concept of the brand. Likewise, the graphic pieces were created from scratch, such as: complementary materials, garment catalog, design of the graphic elements of the capsule collection with the aim of adapting the style and personality of the brand in the garments. The type of material that was obtained was photography and design, communication strategies were proposed, as well as the values that we want to transmit to our public. Finally, a section on lessons learned from the entire development process was presented. Key words: Fashion, Design, Fashion Brand, Brand manual, Identity.